Labeling food allergens in the packaged food pyramid groups in Brazil: analysis of descriptions, ambiguities, and risks - Lopes, Joice Ferreira [UNESP]; de Assis Carvalho, Mary [UNESP]; Machado, Nilton Carlos [UNESP] (FapUNIFESP (SciELO), 2022)
Objective: The aim of this study was to evaluate allergenic labeling components of packaged foods for What is the quality of food labels? and What is the group of Brazilian Food Pyramid that 'May contain' is predominant?. Methods: The photographs of 916 products were obtained, of which 518 were analyzed. Data from each label were evaluated according to Brazilian Food Pyramid Groups (i.e., Cereals, Fruits, & Vegetables; Soybean & products; Milk & dairy products; Meat & eggs; Fats & oils; and Sugars & sweets). Ten items were analyzed in each label, namely, the presence of a list of ingredients, alert phrase for allergy sufferers, grouping of the alert phrase, phrase location, uppercase phrase, the phrase in bold, the color of alert phrase contrasting to the background, adequate font size, do not claim the absence for any allergen with the ingredients, and others factors that make it difficult to read. For the second question, a structured questionnaire was completed, and products were classified into two categories, namely, Contain and May contain. Results: The quality of the label was appropriate, and 69% of packaged foods had at least one allergen. The information May contain were higher in cow's milk (Cereals and Meat & eggs), soy (Soybean & products), and egg protein (Cereals). Soybean & products were the highest insecurity group. Conclusions: Brazilian health professionals can count on goodquality labeling of packaged products. Consequently, they could promote patients' and parents/caregivers' education to consult the labels and manage the risks in processed foods about precautionary allergen labeling. Soybean & products were the most significant insecurity for food choices between Brazilian Pyramid Groups.
Keywords: Allergens; Food hypersensitivity; Food labeling; Industrialized foods